Non-conforming behavior of local people toward non-wood resources in Krau Wildlife Reserve, Malaysia - Mohamad, Mahathir (2012)
The study was carried out at four villages around Krau Wildlife Reserve between January 2008 and Jun 2008. The purpose of this research is to determine the local people non-conforming behavior toward non-wood resource in Krau Wildlife Reserve Area. The main objective of this research is to determine the local people attitude, knowledge and behavioral intention on non-conforming behavior toward non-wood resource in Krau Wildlife Reserve Area. By using structured questionnaires, it was found that average 40% of local people agreed on four (4) statements that relate to attitude toward non-conforming behavior and 60% of local people also agreed to four (4) statements relate to behavior intention toward non- conforming behavior. Through the result, Department of Wildlife and National Park Peninsular Malaysia can make a short term planning regarding enforcement and awareness program other than that is long term planning for the future of Krau Wildlife Reserve Area.